Reduced working memory performance in PTSD and suicide among veterans presenting for treatment. (December 2022) - Albanese, Brian J.; Myers, Ursula S.; Fox, Hailey; Wangelin, Bethany C.
Abstract: Suicide is among the leading causes of death in the United States, underscoring the continued need to understand the mechanisms underlying suicide risk. A growing body of research has examined the role of working memory deficits in suicidal thoughts and behaviors (STBs), yet little research has evaluated putative pathways via which working memory impairments may heighten suicide risk. Elevated posttraumatic stress symptoms (PTSS) represent one plausible mechanism through which poor working memory performance may increase STBs. The present study utilized data from 140 treatment-seeking veterans who presented for an intake evaluation in the PTSD Clinical Team of a large VA Medical Center. Veterans completed self-report measures, a semi-structured PTSD evaluation, and a digit span working memory test. In addition to concurrent suicidal ideation assessed during the intake, additional information regarding past suicide attempts, presence of a safety plan, documentation of past suicidal behaviors, and engagement with suicide crisis lines were collected via electronic medical records. Consistent with hypotheses, a significant indirect path emerged such that poor working memory performance predicted greater suicidal ideation, greater likelihood of a past suicide attempt, and greater latent suicide risk via increased PTSS. However, no direct effect of working memory on STBs or indirect paths of PTSS on STBs via working memory emerged. These findings suggest that the relation between working memory and STBs may be explained by PTSS severity.